2004
DOI: 10.1016/s0955-3959(03)00087-2
|View full text |Cite
|
Sign up to set email alerts
|

Drug use, sexual behaviours and practices among male drug users in Hanoi, Vietnam—a qualitative study

Abstract: A qualitative study was conducted among drug users in Hanoi, Vietnam in May and June 2001 to describe their drug use practices and sexual behaviours, as well as potential factors that might contribute to the recent increase of HIV among them and local sex workers. A total of 63 drug users in five main districts of Hanoi were recruited for in-depth interviews and focus group discussions. The study found that drug users in Hanoi have been engaging in high-risk injecting behaviours and practices. They reported fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Previous studies among IDUs in Hai Phong and Ho Chi Minh City showed that about half the male IDUs had visited FSWs [11,15]. Our qualitative studies among male drug users and FSWs in Hanoi suggested a strong relationship between drug-using FSWs and male drugusing clients and non-client partners [13,14]. This study provides quantitative evidence of this relationship, which has important implications for HIV/AIDS spread in Vietnam.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies among IDUs in Hai Phong and Ho Chi Minh City showed that about half the male IDUs had visited FSWs [11,15]. Our qualitative studies among male drug users and FSWs in Hanoi suggested a strong relationship between drug-using FSWs and male drugusing clients and non-client partners [13,14]. This study provides quantitative evidence of this relationship, which has important implications for HIV/AIDS spread in Vietnam.…”
Section: Discussionsupporting
confidence: 60%
“…Thus, drug use-related characteristics of FSWs have been studied and described thoroughly in these populations [6][7][8][9]. In Vietnam, because the drug use epidemic is relatively current among FSWs and it is difficult to study them, few studies have examined the issue of HIV and drug use among FSWs [2,5,[10][11][12][13][14] and little is known about their drug use behaviors and practices. We conducted a cross-sectional study in Hanoi in 2002 among practising FSWs who were not in drug use or sex worker rehabilitation centers to examine their HIV risk characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This probably reflects that the rate of HIV infection is still highest in Vietnam among IDUs, many of whom are also sex workers (Nguyen et al 2001;Tran et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…34,35 In China, compared to non-IDU sex workers, IDU sex workers have more clients, use condoms less often and are more likely to share syringes. 13,30 The greater likelihood that IDU sex workers will be street-based may also increase the likelihood that they will have IDU clients, and evidence from many regions of IDUs' inconsistent condom use 16,17,[36][37][38][39] suggests that this is a particularly high risk activity. For example, a study in Hanoi showed that street-based sex workers' poverty forced them to accept drug user clients who were rejected by higher status sex workers.…”
Section: Transactional Sex and Commercial Sex Workmentioning
confidence: 99%